Classical and Neo-Pragmatism: William James and Richard Rorty as Models – A Comparative Analytical Study (Comprehensive Journal of Science, 2026)
This study explores and analyzes the trajectory of Pragmatism and its epistemological shifts, starting from a fundamental problem identifying the cognitive gap between classical foundations and the neo-pragmatist orientation، The research aims to elucidate the transition of the philosophical center of gravity from William James’s psychology of experience to Richard Rorty’s linguistic turn, illustrating its impact on the concepts of truth, metaphysics, and the function of philosophy in contemporary society،The study employs a comparative analytical method to deconstruct primary texts and examine the points of rupture and continuity between the two models، The research has yielded several central findings, most notably that the shift from James to Rorty represents a radical transition from truth as a vital utility linked to an individual’s empirical verification, to truth as a discursive consensus based on pragmatics and social agreement، Furthermore, the study reveals that Rorty succeeded in undermining metaphysical representationalism, replacing it with the concept of human solidarity, thereby transforming philosophy from a quest for certainty into a continuous conversation aimed at reducing human suffering، The study recommends the necessity of employing this pragmatic vision to enhance the values of tolerance and cultural dialogue, while suggesting future studies to investigate the impact of neo-pragmatism on contemporary political and moral thought.